2014
DOI: 10.3168/jds.2013-7287
|View full text |Cite
|
Sign up to set email alerts
|

Increasing length of an estradiol and progesterone timed artificial insemination protocol decreases pregnancy losses in lactating dairy cows

Abstract: Our hypothesis was that increasing the length of an estradiol and progesterone (P4) timed artificial insemination (TAI) protocol would improve pregnancy per artificial insemination (P/AI). Lactating Holstein cows (n=759) yielding 31 ± 0.30 kg of milk/d with a detectable corpus luteum (CL) at d -11 were randomly assigned to receive TAI (d 0) following 1 of 2 treatments: (8d) d -10 = controlled internal drug release (CIDR) and 2.0mg of estradiol benzoate, d -3 = PGF2α(25mg of dinoprost tromethamine), d -2 = CIDR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 43 publications
6
51
0
1
Order By: Relevance
“…Vilhelm Magnus and Ludwig Fraenkel performed bilateral ovariectomy or cautery with electrical heat in mated rabbits (Magnus and Simmer, 1972;Wiltbank, 2014). They concluded that the CL was essential for maintenance of pregnancy in rabbits (Wiltbank, 2014). Fraenkel continued these studies into the next decade and concluded that the CL regulates implantation and initial development of the embryo (Fraenkel, 1910).…”
Section: Progesteronementioning
confidence: 96%
See 4 more Smart Citations
“…Vilhelm Magnus and Ludwig Fraenkel performed bilateral ovariectomy or cautery with electrical heat in mated rabbits (Magnus and Simmer, 1972;Wiltbank, 2014). They concluded that the CL was essential for maintenance of pregnancy in rabbits (Wiltbank, 2014). Fraenkel continued these studies into the next decade and concluded that the CL regulates implantation and initial development of the embryo (Fraenkel, 1910).…”
Section: Progesteronementioning
confidence: 96%
“…Fraenkel continued these studies into the next decade and concluded that the CL regulates implantation and initial development of the embryo (Fraenkel, 1910). By 1934, 4 laboratories independently isolated crystalline progesterone (Wiltbank, 2014). Willard M. Allen reported the structure of progesterone and is credited with the hormonal nomenclature.…”
Section: Progesteronementioning
confidence: 99%
See 3 more Smart Citations